2020
DOI: 10.1097/jcma.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid is independently associated with diabetic nephropathy but not diabetic retinopathy in patients with type 2 diabetes mellitus

Abstract: Background: This study aims to investigate the relationship between serum uric acid (SUA) and the severity of diabetic nephropathy (DN) and diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 2961 patients were enrolled in the present cross-sectional study. The severity of DN was determined by 24-hour urinary albumin excretion (UAE), which was classified as normal (UAE <30 mg/24 h), microalbuminuria (UAE: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…In patients with T2D, patients with PDR have higher levels of SUA than those without DR or with NPDR. 21,22 Furthermore, a large-scale prospective study of 749 patients with T2D revealed that SUA levels were associated with a worsening in the severity of DR in Taiwan. 12 Moreover, intravitreal levels of UA were significantly higher in diabetic patients with macular edema than in nondiabetic control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with T2D, patients with PDR have higher levels of SUA than those without DR or with NPDR. 21,22 Furthermore, a large-scale prospective study of 749 patients with T2D revealed that SUA levels were associated with a worsening in the severity of DR in Taiwan. 12 Moreover, intravitreal levels of UA were significantly higher in diabetic patients with macular edema than in nondiabetic control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to DN, neither DR nor DPN was found associated with SUA levels, which was consistent with the previous reports (Xia et al, 2020). On the contrary, a multicenter cross-sectional study in Thailand concludes that SUA is independently associated with peripheral neuropathy in T2DM patients, and elevated SUA should be considered a risk factor for DPN in clinical practice (Kaewput et al, 2020).Two explanations are suggested for the controversial findings.…”
Section: Discussionsupporting
confidence: 86%
“…Elevated SUA levels are independently correlated with the incidences of hypertension and metabolic syndrome (MetS) in some Asian countries including China, Japan, and Korea [2][3][4][5]. For patients with type 2 diabetes mellitus (T2DM), higher SUA levels are associated with the lower estimated glomerular filtration rate (eGFR) and higher prevalence of diabetic nephropathy, but not diabetic retinopathy [6]. Moreover, in general, the decline in SUA levels slows the progression of diabetic kidney disease [7].…”
mentioning
confidence: 99%